Acquired diaphragmatic hernia in an adult male: A diagnostic challenge - Sachdeva, R; Sachdeva, S; Solanki, S (Nepal Journal of Medical Sciences, 2013)
A rare case of acquired diaphragmatic hernia in a middle aged adult male farmer following occupation related weight lifting is described which was missed at initial presentation. High index of suspicious in conjunct with related investigation can clinch early diagnosis. Nepal Journal of Medical Sciences | Volume 02 | Number 02 | July-December 2013 | Page 194-196 DOI: http://dx.doi.org/10.3126/njms.v2i2.8977